Determination of some heavy metal ions with a carbon paste electrode modified by poly(glycidylmethacrylate-methylmethacrylate-divinylbenzene) microspheres functionalized by 2-aminothiazole - Sar, Erdem; Berber, Hale; Asct, Burge; Cankurtaran, Husnu (WILEY-V C H VERLAG GMBH, 2008)
A carbon paste electrode modified with 2-aminothiazole functionalized poly(glycidylmethacrylate-methylmethacrylate-divinylbenzene) microspheres was used for trace determination of mercury, copper and lead ions. After the open-circuit accumulation of the heavy metal ions onto the electrode, the sensitive anodic stripping peaks were obtained by square wave anodic stripping voltammetry (SWASV)). Many parameters such as the composition of the paste, pH, preconcentration time, effective potential scan rate and stirring rate influence the response of the measurement. The procedures were optimized for most sensitive and reliable determinations of the desired species. For a 10-min preconcentration time in synthetic solutions at optimum instrumental and experimental conditions, the detection limit (LOD) was 12.3, 2.8 and 4.5 mu g L-1 for mercury, copper and lead, respectively. The limits of detection may be enhanced by increasing the preconcentration time. For example, LOD of mercury and copper was 4.9 and 1.0 mu g L-1 for fifteen minutes preconcentration time. The sensitivity may also considered to be increased by using a more suitable electrode composition targeting the more conductive electrode with lesser amount of modified polymer for sub-mu g L-1 levels of heavy metal ions. The optimized method was successfully applied to the determination of copper in tap water and waste water samples by means of standard addition procedure. The copper content found was comparable with the certified concentration of the waste water sample. The calibration plots for mercury and lead spiked real samples were also drawn.
Keywords: 2-aminothiazole; carbon paste electrode; square wave anodic stripping voltammetry; heavy metals; tap water; waste water; STRIPPING VOLTAMMETRIC DETERMINATION; PRINTED ELECTROCHEMICAL SENSORS; CHEMICALLY-MODIFIED ELECTRODE; SELF-ASSEMBLED MONOLAYER; TRACE-METALS; SILICA-GEL; MERCURY; ACID; COPPER; PRECONCENTRATION; Chemistry; Electrochemistry